Lymphatic imaging and intervention for chylothorax following thoracic aortic surgery. Issue 34 (21st August 2020) - Chen, Cheng Shi; Kim, Jong Woo; Shin, Ji Hoon; Koo, Hyun Jung; Kim, Joon Bum; Li, Hai-Liang; Kwon, Se Hwan; Ibrahim, Alrashidi; Alhazemi, Almoaiad A.; Chu, Hee Ho
Abstract : Abstract: Reports on lymphatic intervention for chylothorax complicating thoracic aortic surgery are limited. We aimed to evaluate technical and clinical outcomes of lymphangiography and thoracic duct embolization (TDE) for chylothorax complicating thoracic aortic surgery. Nine patients (mean age, 38.9 years) who underwent chylothorax interventions after thoracic aortic surgery (aorta replacement [n = 7] with [n = 2] or without [n = 5] lung resection, and vascular ring repair [n = 2]) were reviewed retrospectively. Magnetic resonance (MR) lymphangiograms were obtained in 5 patients. The median interval between surgery and conventional lymphangiography was 9 days (range, 4–28 days). TDE clinical success was defined as lymphatic leakage resolution with chest tube removal within 2 weeks. MR lymphangiograms revealed contrast leakage from the thoracic duct (n = 4) or no definite leakage (n = 1), which correlated well with conventional lymphangiogram findings. The technical success rate of conventional lymphangiography was 88.9% (8/9); 8 patients showed contrast leakage, while the patient without definite leakage on MR lymphangiography had small inguinal lymph nodes, and thoracic duct visualization by conventional lymphangiography failed. The technical success rates of antegrade and retrograde TDE via pleural access were 75% (6/8) and 100% (3/3), respectively. Clinical outcomes after embolization, as judged by the tube-removal day, were similar between low- (<500 mL/day) and high-output (≥500 mL/day) chylothorax patients. The drainage amount decreased significantly after lymphangiography/TDE, from 710.0 mL/day to 109.7 mL/day (p < .05). The clinical success rate of TDE was 87.8% (7/8). Conventional lymphangiography and TDE yielded high technical success rates and demonstrated encouraging clinical outcomes for chylothorax complicating thoracic aortic surgery.